2020
DOI: 10.1097/corr.0000000000001484
|View full text |Cite
|
Sign up to set email alerts
|

How Did the Number and Type of Injuries in Patients Presenting to a Regional Level I Trauma Center Change During the COVID-19 Pandemic with a Stay-at-home Order?

Abstract: Background During a pandemic, it is paramount to understand volume changes in Level I trauma so that with appropriate planning and reallocation of resources, these facilities can maintain and even improve life-saving capabilities. Evaluating nonaccidental and accidental trauma can highlight potential areas of improvement in societal behavior and hospital preparedness. These critical questions were proposed to better understand how healthcare leaders might adjust surgeon and team coverage of trauma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
88
4
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(113 citation statements)
references
References 18 publications
18
88
4
3
Order By: Relevance
“… 40 , 52 A large reduction was reported in diamond et al‘s US centre 29 (0 v 8%), with a milder reduction in Murphy et al‘s UK centre 54 (0.2% v 1%, p = 1.0). In the US Sherman et al reported an increase in the rate of non-accidental injury (NAI) during the pandemic, 55 and an increase in domestic violence was observed in Rhode's centre. 56 …”
Section: Resultsmentioning
confidence: 99%
“… 40 , 52 A large reduction was reported in diamond et al‘s US centre 29 (0 v 8%), with a milder reduction in Murphy et al‘s UK centre 54 (0.2% v 1%, p = 1.0). In the US Sherman et al reported an increase in the rate of non-accidental injury (NAI) during the pandemic, 55 and an increase in domestic violence was observed in Rhode's centre. 56 …”
Section: Resultsmentioning
confidence: 99%
“…Consistent with previous reports, we identified decreased overall trauma encounters during stay-at-home regulations which was attributable to decreased blunt injuries [ 6 , 7 ]. This included decreases in pediatric orthopedic injuries during the pandemic and likely reflect reduced motor vehicle travel, lack of extracurricular activities, and changes in childcare/observation [6][7][8] .…”
Section: Discussionmentioning
confidence: 99%
“…Since the onset of public health interventions to control the COVID‐19 pandemic there have been many reports outlining the effect of these interventions on general surgical trauma admissions from around the world 1,6–21 . Various methodologies have been employed with commonly short periods of time used and a time period before the interventions used as a comparator.…”
Section: Discussionmentioning
confidence: 99%